Neuromelanin, iron and MRI measurements in midbrain tissues of Parkinson's and Alzheimer's subjects. - Zucca, Fabio A.; Cassidy, Clifford M.; Sturini, Michela; Tuominen, Lauri; Adorni, Fulvio; Cheung, Victoria; Casella, Luigi; Sulzer, David; Pezzoli, Gianni; Isaias, Ioannis U.; Horga, Guillermo; Zecca, Luigi (Frontiers in Aging Neuroscience, 2026)
Background: In Parkinson's disease, decreased neuromelanin and increased Fe concentrations derive from the loss of neuromelanin-containing neurons in the substantia nigra, which is spared in Alzheimer's disease. We aimed to measure neuromelanin and Fe concentrations in post mortem midbrain subregions of patients with Parkinson's and Alzheimer's disease, and to investigate their effect on MRI signals. Methods: We imaged neuromelanin in brain slices of Parkinson's (N = 4) and Alzheimer's disease (N = 7) subjects using neuromelanin-sensitive MRI sequences, compared the results with neuromelanin and Fe concentrations in the same sections, and calculated imaging maps for each subject. Results: Both neuromelanin and Fe concentrations provided unique contributions to neuromelanin-MRI. Compared to Alzheimer's disease, subjects with Parkinson's disease exhibited increased neuromelanin-MRI values in the superior colliculus and periaqueductal gray matter, and higher Fe concentration in the substantia nigra. Conclusion: Results support the use of neuromelanin-MRI to study neuromelanin and Fe in substantia nigra and neighboring regions for investigating patients with Parkinson's disease and other movement disorders.